Phytochemical Profile and Heavy Metal Assessment of Pedada Juice Enriched with Roselle and Beetroot - Nina Hartati; Edi Kurniawan; Meyci Trisna; Rajiyatul Muzni; Nagita Agnes Syuhada; Tiara Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Sonneratia caseolaris, also known as pedada, is a mangrove fruit that is not widely used, despite its great potential for making healthy drinks due to its many beneficial substances. This study aimed to check the plant chemicals and heavy metals in pedada juice that uses natural colors from roselle and beetroot. Tests were conducted to detect certain chemicals, such as phenolic compounds, flavonoids, and alkaloids, and to measure the levels of tin and mercury in the sample. The findings showed that the extracts from pedada, roselle, and beetroot had phenolic compounds, but no flavonoids or alkaloids were found. The presence of phenolic compounds suggests that the drink may have antioxidant properties. In addition, the levels of tin and mercury were measured as 0.026 mg/kg and 0.009 mg/ kg, respectively. These values were well below the maximum allowed by food safety rules, indicating the product is safe for people to eat. The results show that extracts from roselle and beetroot can be good natural colorants for pedada-based drinks and also help improve their healthful qualities without making the product unsafe. Therefore, pedada fruit is a good raw material for making special drinks that add value to mangrove resources. Contribution to Sustainable Development Goals (SDGs): SDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 14: Life Below WaterSDG 15: Life on Land